2016
DOI: 10.1177/1461444815588902
|View full text |Cite
|
Sign up to set email alerts
|

Intimacy and social capital on Facebook: Beyond the psychological perspective

Abstract: Social capital has become a key concept in the study of social network sites such as Facebook. An influential body of literature has emerged which links the accumulation of social capital on Facebook to various psychological traits and depositions. There is a need to augment this work with a more critical, qualitative approach which recognises other key social and technological aspects of Facebook. Based on ethnographic research, I explore how the exchange of social capital on Facebook is significantly influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 48 publications
(63 reference statements)
1
38
0
4
Order By: Relevance
“…Third, as a countermove to the possibility that one's drunkenness becomes translated via online sharing to webpages of wider audiences, our interviewees have developed selfcensoring practices through which they aim to make their drinking an intimate, protected and predictable action (Lambert 2016;cf. Hendriks, Gebhardt, and Putte 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, as a countermove to the possibility that one's drunkenness becomes translated via online sharing to webpages of wider audiences, our interviewees have developed selfcensoring practices through which they aim to make their drinking an intimate, protected and predictable action (Lambert 2016;cf. Hendriks, Gebhardt, and Putte 2017).…”
Section: Discussionmentioning
confidence: 99%
“…We need more research on how representative the different assemblages identified here are among young people; how the use of social media more exactly and concretely reorganizes young people's face-to-face drinking rituals; and on how social media as an actor in various kinds of assemblages transforms young people's spaces and group dynamics in drinking, intoxication, drinking selves and stories. We need to know more about what kinds of drinking-related assemblages social media is translated into among young people from different social backgrounds, cultural contexts, geographical areas, levels of education, digital literacy, and so forth (Lambert 2016); and about the actor-networks that enable young people to drink in virtual realities. A better understanding is needed of how young people's ways of sharing online information and self-presentations differ depending on the nature of the substance their messages deal with; and how practices of self-censorship (Duffy & Chan…”
Section: Discussionmentioning
confidence: 99%
“…Ellison, Steinfield, & Lampe, 2011 p. 873). Indeed, social media use can provide positive benefits for users, including increased social capital (N. Ellison, Steinfield, & Lampe, 2006;Nicole B. Ellison et al, 2011;Lambert, 2016). In addition, Baker and Oswald (2010) found that using social media increased perceptions of friendship quality and provided social support for people who were shy.…”
Section: Peer Group Identificationmentioning
confidence: 99%
“…The conceptual tools of Bourdieu's field theory have been applied extensively to the use of online communication, including attention to habitus and social capital (Julien, 2015;Lambert, 2016;Willig, Waltorp, & Hartley, 2015). Social networking sites provide an opportunity for individuals to develop their social networks and gain social capital, two known factors understood to contribute to psychological wellbeing.…”
Section: Social Networking Sites and Social Mediamentioning
confidence: 99%